A Blockchain-Based Approach to Ensuring the Security of Electronic Data - Patil, Sonali D.; Kathole, Atul B.; Kumbhare, Savita; Vhatkar, Kapil; Kimbahune, 5Vinod V. (International Journal of Intelligent Systems and Applications in Engineering, 2024)
The digitization of conventional medical data poses substantial difficulties for healthcare organizations in the form of electronic health records (EHRs). Doctors and patients alike are used to spending a lot of time querying EHRs for the information they need; however, the data retrieved isn't necessarily relevant to the sought-after one, and access can be denied if that happens. One of the most important parts of the healthcare system is the sharing and keeping of medical records. In the case of a breach, either the confidentiality of patients' information or the accuracy of their medical records would have disastrous consequences. Consequently, it is a top priority to ensure the security of electronic health records. Data integrity, security, and privacy are three areas where modern healthcare infrastructure is infamously lacking in user-friendliness and efficiency. The security and complexity issues may, however, be mitigated with improved electronic health record monitoring and administration. Thanks to the blockchain's decentralized and trustworthy character, this is now a reality in the healthcare industry. The healthcare delivery system is inherently flawed due to issues with data management and the validation and dissemination of information. The main advantage of using blockchain technology for healthcare data management is the improved access it provides to monitoring medications, hospital assets, drug systems, patient information, and so on. Given the critical nature of access to a patient's medical history for dispensing medication, blockchain technology holds great promise for enhancing the present system of healthcare delivery. Consequently, creating a safeguard for medical records based on blockchain technology is of the utmost importance. Last but not least, the performance evaluation shows that the suggested method is more reliable and resilient than the state-of-the-art designs.